Features CES-study method of teaching a foreign language - Nazarova, A. Zh.; Saduova, Sh. M. (Journal of Oriental Studies, 2016)
Method of the Case is being sought in the form variant of an interactive method or as a small game with signs of professional activity. training material for those studying the language, in this technology represented through a problematic situation, when a student decides to talk to a professional turkish language he is learning through active research and creative activity.